(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2024)
Chemical control of Plutella xylostella pests is no longer feasible because cabbage is a product directly consumed by consumers. A better alternative is biological control by utilizing parasitoids. The Community Partnership Program Cluster 2 (PKM_K2) was carried out with the aim of conducting socialization to the Lokon farmer group in Kakaskasen II Village, Tomohon City so that they can learn how to propagate the parasitoid Diadegma semiclausum, which can be used to control P. xylostella pests. The use of the parasitoid D. semiclausum to directly control P. xylostella pests can minimize chemical insecticide deposits on products consumed by consumers. The implementation method is in the form of direct socialization and discussion with the Lokon farmer group. The results of the collaboration between the Lokon Farmer Group and the PKM_K2 Activity Proposer Team of the Faculty of Agriculture, Unsrat have succeeded in transferring knowledge as seen that the farmer group is very responsive in participating in this activity.